Liquidity provision as a monetary policy tool: The ECB's non-standard measures after the financial crisis - Dominic Quint; Oreste Tristani (Deutsche Bundesbank, 2017)
We study the macroeconomic consequences of the money market tensions associated with the financial crisis in the euro area. In a structural VAR, we identify a liquidity shock rooted in the interbank market and use its impulse response functions to calibrate key parameters of a Smets and Wouters (2003) closed-economy model augmented with a banking sector à la Gertler and Kiyotaki (2010). We highlight two main results. First, an identified liquidity shock causes a sizable and persistent fall in investment. The shock can account for one third of the observed, large fall in euro area aggregate investment in 2008-09. Second, the liquidity injected in the market by the ECB played an important role in attenuating the macroeconomic impact of the shock. According to our counterfactual simulations based on the structural model, in the absence of ECB liquidity injections interbank spreads would have been at least 200 basis points higher and their adverse impact on investment would have been more than twice as severe.
Keywords: E44; E58; 330; ECB; euro area; financial crisis; financial frictions; interbank market; non-standard monetary policy